2013
DOI: 10.1515/hf-2012-0199
|View full text |Cite
|
Sign up to set email alerts
|

Storage-induced emissions from different wood species

Abstract: In this study, the extractive contents and the storage-induced emissions from chips of Salix alba, Betula pendula, Populus tremula, and Alnus glutinosa are compared with emissions from Pinus sylvestris chips. Soxhlet extraction was performed, and carbon monoxide (CO) and O 2 concentration in the gas phase as well as gas chromatography-mass spectrometry analysis of volatile organic compounds were analyzed. Pinus sylvestris showed the highest extractive content in the petrol ether fraction and emitted CO in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…226 For biomass materials, it was postulated that CO is produced from auto-oxidative degradation of fats and fatty acids 12,244 and suggested that the oxidation of the extractives particularly the fatty acids could be the primary reason for CO emission and simultaneous O 2 depletion, 17 since the content of the extractives may correlate with CO emission and O 2 consumption. 243 It was found, however, that the content of fatty acids in wood pellets is too low to account for the observed high concentration of CO off-gassing. 14,45,229 A two-step path was therefore proposed for the production of CO from storage wood pellets: the autooxidation of the extractives, mainly fatty acids as well as terpenes, forms aldehydes and produces hydroxyl ( • OH) radicals, and the subsequent • OH oxidation of hemicellulose through a chain reaction produces a bulk mass of CO. 231 The mechanism was proven by ozonolysis of wood fiber to eliminate unsaturated hydrocarbons so as to depress the formation of the radicals and consequently reduce CO production.…”
Section: Low Temperature Chemical Oxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…226 For biomass materials, it was postulated that CO is produced from auto-oxidative degradation of fats and fatty acids 12,244 and suggested that the oxidation of the extractives particularly the fatty acids could be the primary reason for CO emission and simultaneous O 2 depletion, 17 since the content of the extractives may correlate with CO emission and O 2 consumption. 243 It was found, however, that the content of fatty acids in wood pellets is too low to account for the observed high concentration of CO off-gassing. 14,45,229 A two-step path was therefore proposed for the production of CO from storage wood pellets: the autooxidation of the extractives, mainly fatty acids as well as terpenes, forms aldehydes and produces hydroxyl ( • OH) radicals, and the subsequent • OH oxidation of hemicellulose through a chain reaction produces a bulk mass of CO. 231 The mechanism was proven by ozonolysis of wood fiber to eliminate unsaturated hydrocarbons so as to depress the formation of the radicals and consequently reduce CO production.…”
Section: Low Temperature Chemical Oxidationmentioning
confidence: 99%
“…The measured gaseous compounds include CO, CO 2 , CH 4 , VOCs, and O 2 . The materials tested are mainly pellets of softwood, hardwood, blended wood, and straw–wood mixture ,, ,, and also include sawdust for pellet production, wood chips, , wood bark, torrefied and steam explored wood pellets, , agricultural residues, switchgrass, and sewage sludge. , The temperature for the measurements ranges from room temperature to near the ignition point, covering the entire range of chemical oxidation contributing to self-heating prior to spontaneous ignition. The temperature inside the sample may be monitored mostly to ensure isothermal conditions ,, and seldom to detect self-heating.…”
Section: Low Temperature Chemical Oxidationmentioning
confidence: 99%
See 1 more Smart Citation